Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acs.est.2c01077
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Annual Average Traffic-Related Air Pollution Concentrations in the Greater Seattle Area from a Year-Long Mobile Monitoring Campaign

Abstract: Growing evidence links traffic-related air pollution (TRAP) to adverse health effects. We designed an innovative and extensive mobile monitoring campaign to characterize TRAP exposure levels for the Adult Changes in Thought (ACT) study, a Seattle-based cohort. The campaign measured particle number concentration (PNC) to capture ultrafine particles (UFP), black carbon (BC), nitrogen dioxide (NO 2 ), fine particulate matter (PM 2.5 ), and carbon dioxide (CO 2 ) at 309 roadside sites within a large, 1200 land km … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 83 publications
0
38
0
Order By: Relevance
“…Hankey et al (2015), for example, conducted ~85 hours of bicycle-based mobile measurements of UFP, BC, and PM2.5 to build LUR models in urban Minneapolis. Blanco et al, (2022) in a stop-and-go mobile monitoring configuration, measured air pollution levels (UFP, BC, NO2, PM2.5, CO2) at 309 roadside sites over one year period in Greater Seattle Area.…”
Section: Discussionmentioning
confidence: 99%
“…Hankey et al (2015), for example, conducted ~85 hours of bicycle-based mobile measurements of UFP, BC, and PM2.5 to build LUR models in urban Minneapolis. Blanco et al, (2022) in a stop-and-go mobile monitoring configuration, measured air pollution levels (UFP, BC, NO2, PM2.5, CO2) at 309 roadside sites over one year period in Greater Seattle Area.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations were winsorized at the site level once (not after each subsample, see Section ) by setting values below each site’s 5th or above 95th quantile concentration to that threshold, respectively, to reduce the influence of a few extreme observations on annual averages. We previously showed that winsorizing prior to averaging slightly improved PNC and PM 2.5 models due to the reduction of influential points, while using approaches completely robust to influential points (i.e., medians), produced worse-performing models of pollutants with already limited spatial variability like CO 2 …”
Section: Methodsmentioning
confidence: 99%
“…New PLS components were calculated for each model (five models per sampling campaign for fivefold cross-validation and one for test set validation). We selected this subset of covariates from 348 original covariates because these had sufficient variability and a limited number of outliers in the training-validation set . The models were ln ( con c i ) = α + m = 1 M θ m Z mi + ε i where conc i is the pollutant concentration at the i th location, Z m are the first two PLS principal component scores ( M = 2), α and θ m are estimated model coefficients, and ε is the residual term with mean zero and a modeled geostatistical structure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations